URGENSI PENDIDIKAN ANTIKORUPSI TERHADAP PENCEGAHAN KORUPSI DALAM PENDIDIKAN DASAR (Universitas Suryakancana, 2020)
Corruption eradication in Indonesia is still not optimal and still prioritizes repressive actions against corruption cases that have occurred. The implementation of such efforts is ineffective in eradicating corruption because corruption has taken root in the legal culture of society. One of the ways that can be implemented in efforts to eradicate corruption is to prevent corruption which can be done by providing anti-corruption education, especially for students at the primary education level. Primary education is the focus of providing anti-corruption education because it is at this level that the character building of a person, and anti-corruption education is actually character education. Keywords : Corruption Prevention, Corruption Crime, Anti-Corruption Education.